Hearing and reading: responding to the Articles of Perth in the 1618 court sermons of Lancelot Andrewes and John Buckeridge. Issue 2 (4th May 2021) - Knapp, Travis J.
ABSTRACT: Although we often study the printed text of sermons, most originated as oral performances. Because the apparatus of printed versions tends to amplify the political and polemical aspects of a sermon, this focus has led some scholars to read sermons as they would polemical tracts, while ignoring an important purpose of the genre—the spiritual edification of hearers. This essay considers both oral and printed rhetorical effects in an examination of three English court sermons, all published in 1618. The study reveals that the oral rhetoric of the sermon speaks to an immediate need for individuals to reform their worship practices by incorporating both internal and external modes of piety into personal worship. The polemical and political attitudes, by contrast, would have been muted and implicit to hearers. As a result, I argue, a disproportionate emphasis on the printed text has dulled our sensitivity to early Laudianism's moderate appeals.